Statistical investigation into the flow field of closed aquaculture tanks aboard a platform under periodic oscillation. (15th March 2022) - Cui, Mingchao; Li, Zhisong; Zhang, Chenglin; Guo, Xiaoyu
Abstract: Floating aquaculture platform is expected to be a sustainable way for offshore aquaculture, which is attracting worldwide attention. The flow field (e.g., velocity magnitude, traveling distance) deserves investigation to evaluate the fish-friendliness from the view of the hydrodynamics. The statistical analysis methods are employed to quantify the probabilities of hydrodynamic parameters. In this paper, the platform is subject to the oscillation of roll and pitch. The influence of oscillating angle and radius on the hydrodynamic parameters is explored with Computational Fluid Dynamics. The spatial characteristics of flow fields are quite different between the pitching scenario and the rolling scenario. The average traveling distance of water increases linearly with time. In the spectral domain of flow fields, multi-mode characteristics are observed in asymmetric oscillating scenarios. The probability-based accumulated hydrodynamic parameters are not sensitive to the oscillating radius in pitching scenarios. While in the rolling scenarios, the parameters increase significantly with the rolling angles. Considering the sensitivity of the hydrodynamics parameters on motion parameters, it is a reasonable way to satisfy a suitable velocity field by adjusting the rolling condition to alleviate sloshing. Highlights: Statistical method and FFT analysis are employed to study the flow characteristics. Temporal mass-averaged mean kinetic energy exhibits multi-frequency responses. Velocity magnitude and water traveling distance are statistically analyzed. Oscillating angle evidently affect the velocity magnitude and water traveling distance.